Slang in Its Cultural Environment - Gevorgyan, Gurgen (Armenian Folia Anglistika, 2008)
The non-standard vocabulary of the English language has always been an interesting area of research. The 20th century saw an increase in this interest. Non-standard words and phrases started finding their ways into dictionaries, linguistic journals and even daily newspapers. However, it is still difficult to draw a strict distinction between the standard and non-standard vocabulary, since, as is known, language undergoes constant development. As a result, the same word that used to be considered as non-standard about 20 years ago, can be viewed as quite standard nowadays. Slang is a non-standard form of English. It is a lexical novelty in a certain cultural environment. It is equally existent in all languages and cultures. Many Indo-European languages are rich in slang words and phrases.